The marigold mess - Jules, Jacqueline, 1956- (Jules, Jacqueline, 1956- Sofia Martinez., 2015)
Instead of the usual dusting Sofia volunteers to wash the car--but when she leaves the hose on her mother's marigolds get flooded and she calls on her sisters to save the situation.